Pengaruh Kesehatan, Upah Minimum, Dan Pendidikan Terhadap Kemiskinan Di Jawa Timur 2020-2022 - Reza Firmansah; Mohammad Rizal; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the effect of health, minimum wages and education on poverty in East Java 2020-2021. The type of research used is quantitative. The method used in this research is panel data analysis. Panel data regression is a regression that combines cross section data and time series data. Estimation of panel data regression can be done through 3 estimates, namely CEM, FEM and REM. Data analysis in this study used the help of Eviews 10. In this study, it was found that health, minimum wages and education have a simultaneous effect on poverty. Health has a partial effect on poverty, minimum wage has no partial effect on poverty and education has no partial effect on poverty. Keywords: Health, Minimum Wage, Education, Poverty